Execution at midnight [videorecording] - Thebaut, Jim.; Arts and Entertainment Network (New York).; Evergreen Films, Inc. (N.Y. A & E Network, 1992)
Examine many Americans call justice and other term barbarity. Interviews inmates living on death row, all of whom were convicted of murder and have been on death row from six to twelve years.
Documentary.
VHS.
Editor, Robert McDonald ; Host, Bill Kurtis ; Investigative Reports producers, Jonathan Towers, Richard Leslie; executive producer for A & E, Michael Cascia.
Keywords: Death row -- United States; Capital punishment -- United States; Execution and executioners -- United States